Knowledge and social engagement change in intention to be screened for colorectal cancer. Issue 5 (4th July 2018) - Molina, Yamile; Briant, Katherine J.; Sanchez, Janeth I.; O'Connell, Mary A.; Thompson, Beti
ABSTRACT: Objective: Innovative technologies have been used to promote colorectal cancer (CRC) screening among the underserved. However, the impact of these innovative technologies on knowledge and social engagement likelihood as they relate to subsequent intention to be screened across different populations has not been fully explored. Design: Using a pre–post-test design with an inflatable walk-through colon, we assessed changes in knowledge and social engagement likelihood across populations and their associations with intention to be screened in two community settings. One was a community setting in Washington State (WA); the other, a college campus in New Mexico (NM). Differential effects on knowledge and social engagement likelihood were examined across demographic groups (race/ethnicity, gender, age, education, insurance status, and geographic region). Finally, we assessed if changes in knowledge and social engagement likelihood were associated with CRC screening intention. Results: NM males had greater gains in CRC knowledge than NM females; in WA, Hispanics, younger, less educated, and uninsured participants had greater gains in knowledge. NM females and younger WA participants were more likely to discuss CRC with their social networks than NM males and older WA participants. In WA, Hispanics and older adults reported greater intention to be screened for CRC. Change in social engagement likelihood, but not knowledge, was associated with intention to be screened. Conclusions: The effectiveness of health promotion technologies on knowledge and social engagement may vary across different demographic characteristics. Further, the importance of social engagement likelihood in interacting with intention to be screened was substantiated.